Digital Marketing Innovation and the Role of Information Systems in Enhancing MSME Market Expansion - Muammar Revnu Ohara; Suherlan Suherlan; Wahyuni Sri Astutik (Politeknik Ganesha Medan, 2024)
Digital marketing has become one of the essential elements in supporting the growth and sustainability of micro, small, and medium enterprises (MSMEs) in the modern era. Along with the development of information technology, digital marketing offers opportunities for MSMEs to expand their markets and increase product visibility to a broader range of consumers. In this context, innovation in digital marketing becomes a key factor driving MSMEs' success in achieving sustainable growth. This study aims to further review how digital marketing innovation and the use of information systems can support MSME market expansion. This research employs a literature review approach focusing on qualitative methods. It does not involve primary data collection but instead relies on relevant and up-to-date sources from various scholarly articles. The data used in this study is sourced from Google Scholar with a publication range from 2013-2024. The study concludes that digital marketing innovation and the use of information systems play a crucial role in expanding MSME markets. Digital marketing innovation allows MSMEs to reach consumers more broadly and efficiently, utilizing digital platforms such as social media, e-commerce, and websites. Meanwhile, information systems help improve operational efficiency, data management, and more accurate decision-making based on data analysis. Case studies of Batik Trusmi, Maicih, and Sociolla show that MSMEs adopting these innovations can expand their market share, increase customer loyalty, and compete more effectively in both domestic and international markets.